ҚАРАҚАЛПАҚ ХАЛЫҚ ДӘСТАНЫ «ШӘРЬЯР»ДЫҢ СЮЖЕТЛИК ҚАТЛАМЛАРЫ (Дәстан генезисине тийкар болған аўыспалы сюжетлер ҳәм олардың поэтикалық хызмети мәселеси) - Кенесбаева, Ш. (ILIM hám JÁMIYET, 2019)
The article deals with the origin of plot layers of the dastan «Shariyar», there were analyzed the transferred fairy-tale plots typical for literature and folklore of the East and West. On the basis of facts it is stated that these plots served as an ideal-aesthetic sourse in creation of the epos «Shariyar». The epos «Shariyar» is an aesthetic factor like the work «Fairy-tale about tsar Saltan» by A.S.Pushkin.